The Role Of Technology In Education - Anwar, Aang Solahudin; Mardisentosa, Bambang; Williams, Alexander (Pandawan Sejahtera Indonesia, 2021)
Here modern technology is defined as knowledge that is transformed into products, processes, services and organizational structures. Technology is always juxtaposed with the term science. Science is a human effort to understand the phenomena and facts of nature, and to preserve that knowledge conceptually and systematically. While technology is a human effort to use science for the benefit and welfare. Because of this relationship, the development of science is always related to technological developments, and vice versa. The development of science and technology has an exponential characteristic, which is getting faster and faster, because the results of one stage become the basis and reason for the next stage. It is not surprising that not only is its development accelerating but the role of science and technology in modern society is increasing in importance. The development of science is active in all fields, namely health, agriculture, economics, social sciences, natural sciences and so on.